Assessing The Knowledge, Attitude and Practices of Malaria Prevention and Treatment in Mansa District, Luapula Province, Zambia - Lillian Mambwe Mutesu; Rodrick Sakamba; Stanley Nyirenda; Kingford Chimfwembe (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Malaria continues to be a major public health problem in Zambia with more than 16 million people at risk and 2015 estimates show that there were over 5 million malaria cases. Children under five years and pregnant women are at the greatest risk. Despite Zambia’s interventions including universal insecticide-treated bed-net (ITN) coverage and indoor residual spraying (IRS) in targeted areas strides in the fight against malaria, the situation in Luapula Province is totally different with the highest incidence in pregnancy, 131/1000 in 2013, 207/1000 in 2014, and 177/1000 in 2015. This research therefore assessed the knowledge, attitudes, and practices of malaria prevention and treatment in Mansa, Luapula province of Zambia. Material and Methods: A descriptive cross-sectional study design adopting both qualitative and quantitative study approaches was used on 270 study participants who included community members, pregnant women and health personnel in Mansa ward of Mansa district. The participants were sampled using simple random and purposive sampling techniques. Data was collected using questionnaires, interview guides, and focus group discussions. The quantitative data was analyzed using SPSS statistical software, while the qualitative was thematically analyzed. Results: Out of the 270 participants, knowledge of malaria transmission being due to mosquito vector was very high and seen in 270 (100%), however, other perceptions of transmission were; drinking contaminated water 3(1.1%), eating a lot of mangoes 7(2.6%) and coming in contact with a sick patient 207(76.7%). Participants negative attitudes stood at 196 (72.6%) and bad practices was 153(56.7%). Education level was strongly associated with knowledge (p=0.000), attitudes (p=0.001) and practices (p=0.004). Conclusion: Even though knowledge levels on malaria were high and comparable to other studies, however, some attitudes and practices were negative among the participants. On the contrary, healthcare providers had the right attitude towards malaria prevention and control. Community Health Workers are very important in the fight against malaria. The study recommends that creating health promotion messages taking into account the illiterates, involvement of traditional leaders, and giving incentives to community health workers can help in the fight against malaria in Luapula Province.